Development of a management-based ranking of beaches - Oliveira, Elaine (2024)
Beach rankings are very frequent on the internet; however, the information provided on how these rankings are made is often unclear and their content is mostly subjective. In addition, the vast majority of these rankings do not take into account the fact that beaches are coastal eco-systems. The aim of the research was to develop an objective framework to rank the quality of beaches worldwide. The framework integrates indicators to assess the socio-ecological system quality and can be used as a basis for effective beach management. The methodology involved the collection, evaluation and grouping of indicators into domains and categories. Moreover, a measurement technique and a 5-point rating score for each indicator was used. Weights were calculated for different beach types using an analytical hierarchical process and the methodology was validated by a focus group of beach management experts. The quality value of each beach was calculated through equations and the results were presented in graphs inspired by the Circles of Sustainability and the Ocean Health Index. The theoretical application was tested on Portuguese beaches. The framework presents a holistic assessment of four domains: Recreation, Protection, Conservation and Sanitary. The resulting Beach Ranking Framework (BRF) is an objective, holistic framework designed to communicate with society, unlike the existing beach quality assessments.